Living, Learning, and Dying by Water: Materialist Jamaican Environment in A Tall History of Sugar by Curdella Forbes - Valovirta, Elina (Taylor & Francis, 2025)
Water is a crucial element in A Tall History of Sugar by Curdella Forbes (Citation2019), which spans Jamaica’s recent history from its independence in 1962 to the present day. The novel highlights the importance of the sea and Caribbean and Atlantic waterways in articulating notions of living, learning and dying by water, where all these main events in the story occur. The essay argues that water as a materialist force shapes the narrative and helps tell the story of Moshe and Arrienne, two childhood friends growing up in rural Jamaica, who later marry and build a life together in the middle-class hillside of Kingston, Jamaica. Water in the novel serves a function, like helping Arrienne learn the predatory sexuality of an intrusive teacher on a biology lesson. Ultimately, water helps build a reparative stance on death, tying together environmentally and politically conscious African-Jamaican storytelling with the agentic quality of water.